Can blockchain revolutionize international trade? - Ganne, Emmanuelle (World Trade Organization GenevaCH, 2018)
This publication seeks to demystify the Blockchain phenomenon by providing a basic explanation of the technology. It analyses the relevance of this technology for international trade by reviewing how it is currently used or can be used in the various areas covered by WTO rules.